c.1 - "Lincoln, Yvonna S. (ed.)" (London, 1985)
The transition from viewing organizations as bureaucracies toward seeing them in metaphoric terms is a contemporary break with past organizational theory. But to investigate the similarities between real organizations and the metaphors describing their functions and context, a shift in both methods of inquiry and organizational theory must take place. The original essays in this volume explore the paradigm shift at three levels: (1) an overview of historical roots; (2) an explication of terminology, metaphors, and constructs; and (3) the practical application of these new organizational inquiry methods, especially for actual research practices and policy analysis applications. "An up-to-date picture of what is going on in the field. . . . Worth reading if one has a serious interest in organizations." --European Journal of Operational Research
Keywords: Social Interaction